Prestasi Belajar Siswa Kelas V Sekolah Dasar Dalam Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions - Annisa, Imra; Fitria, Yanti; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is aimed at investigating student learning achievement at elementary school class V in cooperative learning with Cooperative Learning WithStudentTeams Achievement Divisions Type. The kind of research was Quasi Experimental Design. The independent variable was cooperative learning with StudentTeams Achievement Divisions Typemodel whereas the dependent variable was study achievement. The technique of taking sample was cluster random sampling. Data is processed by using different test ( t-test). From t test analysis (t-test) obtained tcount = 3.08 while ttabel at significance level α 0,05 is 1,980. Thus tcount is bigger than ttable that is 3.08> 1,980. The results showed the application of StudentTeams Achievement Divisions Typecooperative learning model gives a significant influence on student achievement on material topic of ethnic and cultural diversity of the nation.